POPULATION DENSITY OF BLACK FRANCOLIN (FRANCOLINUS FRANCOLINUS L.) IN KALA CHITTA RANGE, PAKISTAN - A. Basit; M. Anwar; B. A. Rakha; M. S. Ansari; N. Munawar; A. Akhter (Journal of Animal and Plant Sciences, 2021)
Black francolin or Black partridge (Francolinus francolinus L.) is distributed throughout Pakistan including Indus plains, Baluchistan, Punjab and Khyber Pakhtunkhwa provinces. Black francolin has been described as common or Least Concern in IUCN Red List of Threatened Species (2018). There was no documented information available on population density of Black francolin in various habitats of Kala Chitta hills of Pothwar region, Pakistan. Therefore, present study was designed to investigate the population of Black francolin in study area to devise conservation measures. Based on the reconnaissance survey, three representative sites were selected to estimate the population of black francolin in its potential habitat in Kala Chitta hills. Observations were taken by direct sighting using “Visual Encounter Method (VEM)”. The observations were taken along three fixed transects, having a length of 300 m and width varying from 20 to 50 m were laid down at each site to record the birds on or near the line. Overall, population density of Black francolin was recorded 1.06 birds/ha. Highest population density (2.19 birds/ha) was recorded in mountainous forest and associated grassland. While, population density of 0.84 and 0.15 birds/ha was recorded in open cultivated land and wetlands associated vegetation, respectively. It is concluded that Black francolin population density is affected by habitat characteristics in Kala Chitta Hills. Therefore, habitat characteristics must be considered while devising conservation plan for Black Francolin.
Keywords: Francolinus francolinus; Population; Kala Chitta; wetlands; mountainous forest